Influence of Stenosis Shape, Lesion Length, Eccentricity, and Diameter on Fractional Flow Reserve in Coronary Arteries: A CFD Study - Symon Feolino; Aloyod, Murshied; Kim Aaron Bravo; Bonifacio Doma (International Journal of Computational and Experimental Science and Engineering, 2025)
Arterial stenosis, condition characterized by abnormal narrowing of blood vessels, disrupts blood flow and raises the risk of serious cardiovascular complications. Previous studies indicate highlight that stenosis geometry, lesion length and eccentricity can significantly impact on blood flow characteristics; however, detailed analyses on the combined effects of these parameters remain limited. This study aims to investigate the effects of different stenosis geometries, lengths, and eccentricities on artery’s fractional flow reserve (FFR), velocity magnitude and static pressure. Using two stenosis levels (80% and 90%) and two lesion lengths (10 mm and 20 mm), arterial flow across rectangular, elliptical, triangular, and trapezoidal geometries are computationally modelled under both concentric and eccentric configurations. The results show that abrupt shapes, such as triangular and rectangular lesion, create high velocity spikes and pressure gradient near lesion edges, resulting in elevated shear stress. Shear stress and flow disturbance were reduced by smoother shapes, especially elliptical and trapezoidal configurations, which were linked to more gradual velocity and pressure transitions. Additionally, concentric models generally yield higher FFR values, indicating better flow preservation. Rectangular and trapezoidal shapes showed lower FFR values, particularly in eccentric conditions with severe stenosis, while triangular shapes showed relatively high FFR values, suggesting a lower impact on flow.